2019
DOI: 10.1039/c9mt00223e
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of myocellular copper-trafficking proteins and mitochondrial copper enzymes repairs cardiac function in rats with diabetes-evoked heart failure

Abstract: Diabetes impairs systemic copper regulation, and acts as a major independent risk factor for heart failure (HF) wherein mitochondrial dysfunction is a key pathogenic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Furthermore, TNNI3, a gene encoding cardiac sarcomere troponin I protein, was examined as a regulating gene for cardiac proteins necessary for proper assembly of the cardiomyocytes. Changes in TNNI3 are a well-known cause of cardiomyopathy (Mirza et al 2005, Rai et al 2009) and its expression showed down-regulation in cardiac muscles of type2 diabetes (Howarth et al 2011) in which Cu plays an important role in its development due to defective myocellular Cu regulation (Zhang et al 2014, Zhang et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TNNI3, a gene encoding cardiac sarcomere troponin I protein, was examined as a regulating gene for cardiac proteins necessary for proper assembly of the cardiomyocytes. Changes in TNNI3 are a well-known cause of cardiomyopathy (Mirza et al 2005, Rai et al 2009) and its expression showed down-regulation in cardiac muscles of type2 diabetes (Howarth et al 2011) in which Cu plays an important role in its development due to defective myocellular Cu regulation (Zhang et al 2014, Zhang et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that Cu de ciency (CuD) could be a leading cause of adverse cardiac events including ischemic and hypertrophic disorders (DiNicolantonio et al 2018, Li et al 2018, Liu et al 2018. Also, the alteration in the myocardial Cu acquisition mechanism was recently pointed out as the key factor in diabetes-induced heart failure in rats (Zhang et al 2020). Thus, during heart failure, the low level of left ventricular Cu concentration could aggravate the development of cardiac dysfunction due to extensive changes in myo brillar and mitochondrial morphology and distribution (Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated extracellular Cu 2+ in DM cardiomyopathy is likely loosely bound to extracellular matrix components, such as collagens [ 168 , 169 ]. Interestingly, in rodents and humans with DM cardiomyopathy, Cu 2+ -selective chelators, including trientine and triethylenetetramine (TETA) dihydrochloride, prevent excessive cardiac collagen deposition, improve cardiac structure and function, and restore antioxidant defense by promoting copper excretion [ 168 , 174 , 175 , 176 , 177 , 178 ]. Zhang et al reported that the expression of the Ctr1 gene was downregulated in hearts of rats with DM, which is consistent with impaired cardiac copper uptake in DM [ 176 ].…”
Section: Copper Deficiency and Heart Diseasementioning
confidence: 99%
“…These data suggest that TETA normalizes cardiac copper homeostasis and restores cardiac function in DM by restoring expression and localizations of copper transporters and copper-binding proteins. In addition, TETA restores mRNA and protein expression of copper chaperones, including COX11, COX17, CCS, and SOD1 and, thus, restores copper availability and trafficking, and improves cardiac functions in hearts of rats with DM [ 175 ]. Although the highly selective Cu 2+ chelator trientine efficiently treats DM cardiomyopathy, long-term clinical studies are necessary to determine whether the improvement of cardiac function by trientine is associated with long-term benefits for mortality.…”
Section: Copper Deficiency and Heart Diseasementioning
confidence: 99%
“…Bioinformatics results have shown that cytochrome c oxidase assembly homologue 11 (COX11) is a target of miR-10a-3p. It participates in metabolism, apoptosis, energy supply, and reactive oxygen production in organisms and plays an important role in cancer and respiratory system diseases (15,16). There is no report on the function of COX11 in MPP.…”
Section: Introductionmentioning
confidence: 99%